PERSPEKTIF ISLAM TERHADAP PEMERKOSAAN DALAM PERNIKAHAN - Muhammad Khoirul Anwar; Aghnia Nuha Zahidah; Khildaniyah Ridho (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This paper aims to analyze the occurrence of marital rape or rape in marriage according to the view of the Qur'an. The term marital rape is used for an incident where a husband forcibly has sexual relations with his wife. It is called forcing because in having sexual relations the wife does not want it. Then the term became popular in Islamic studies which were discussed massively by progressive groups to find their theological legitimacy. This paper was written using Hasan Hanafi's thematic interpretation study method by using the starting point from events to text (minal waqi' ila an-Nash). The conclusion of this paper is that in Islam, especially in the Qur'an, there are no terms related explicitly to marital rape. Precisely with the existence of marriage, it signifies the validity of the social relationship between men and women in a way that is makruf and each is under the auspices of marriage rights. So that in marriage there is essentially no idea of ​​rape in marriage. This article agrees with the findings of Marlia and Dzuhayatin who reject the existence of bias in interpretation of the verses on the relationship between husband and wife that is not equal